Isports: A statistical tool for online talent identification - Maiorano, A. C.; Ara, A.; Louzada, F. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The main goal of this paper is to present an innovating online system, built through free software and statistics tools that allow a comparison of individuals in any sport modality. Particularly, this shown study is focused in the performance evaluation in soccer, using univariate and multivariate statistical methods. The univariate approach is given by the Z- CELAFISCS methodology and the multivariate is given through a novel construction of indicators using Principal Component Analysis, Factor Analysis and Copulas. The created system shows many dynamic online reports that allow us to observe the results of the subjects in the tests and who is more suitable for the practice of this sport.